The association between sleep quality and anemia incidence among junior high school students: A cross-sectional study - Wulandari Wulandari; Sukardin Sukardin; Febriati Astuti (Yayasan Pendidikan Kardin Assidiq, 2025)
Background: Anemia is a common health issue among adolescents, particularly due to iron deficiency. Poor sleep quality is believed to contribute to the prevalence of anemia; however, the relationship between the two remains a topic of debate. Objective: This study aims to determine the relationship between sleep patterns and the incidence of anemia in adolescents at a Junior high school. Method: This research employed a quantitative method with a cross-sectional approach. The study population consisted of 161 students, from whom a sample of 115 respondents was selected using a purposive sampling technique. Data collection involved administering the Pittsburgh Sleep Quality Index (PSQI) questionnaire to assess sleep quality and measuring hemoglobin (Hb) levels using the Easy Touch GCHB tool. Data analysis was performed using the Chi-Square statistical test. Results: The findings revealed that the majority of respondents (55.7%) experienced poor sleep quality, and 44.3% were found to have moderate anemia. The results of the bivariate analysis using the Chi-Square test indicated no significant relationship between sleep patterns and the incidence of anemia among junior high school students, with a p-value of 0.217 (>0.05). Conclusion: Sleep quality does not significantly affect the incidence of anemia in junior high school students. Other factors, such as diet, iron intake, and physical activity, may have a greater impact on hemoglobin levels. Therefore, it is essential to enhance health education related to nutrition and establish good sleep patterns to help prevent anemia in adolescents.